Uncertainty in Cost Estimating for Syrian Building Projects - Jamal Omran; Bassam Hassan; Rana Khrbotly (Tishreen University, 2019)
It has been observed that the local construction companies have several problems, which resulting from underestimate of initial cost ,and that force them to charge with additional works within the contract  or to organize additional contract - Addendums  which confuse  the financing policy of the company , obstruct organization work of the project , continue working and achieve the works in the exact date . Statistical methodology was adopted to estimate the initial cost of the project, taking into account the risk arising from deviations in the appreciation of the method of calculating the estimate and the cost driver, so we were able to put the values of an initial contract for the project in close enough to final values, as well as to determine the reserve that was required to ensure not to exceed the final cost and an acceptable degree of accuracy. It has been reached on a set of models that reflect the relationship between cost and specific cost, by examining a sample of 86 schools were constructed between 1998-2007 and by taking advantage of statistical methods, and the analysis and reduce the impact of uncertainty in each model , which resulting from estimation method and model inputs statistically .